An Improvement of Catalytic Converter Activity Using Copper Coated Activated Carbon Derived from Banana Peel - Abdul Hamid; Misbakhul Fatah; Wahyu Budi Utomo; Ike Dayi Febriana; Zeni Rahmawati; Annafiyah Annafiyah; Aurista Miftahatul Ilmah (International Journal of Renewable Energy Development, 2023)
The emission of nitrogen oxide (NOx), nitrogen monoxide (NO) and carbon monoxide (CO) from vehicle exhaust gas generates an adverse effect to the environment as well as the human health. Therefore, the need to reduce such emission is urgent. The decrease of the emission can be achieved through the use of catalytic converter. This study explains the application of catalytic converter prepared from activated carbon to enhance the activity through its adsorption ability. The activated carbon was derived from banana peels after heating them up at 400 ºC for 1.5 hours and activation using natrium hydroxide (NaOH). Several techniques including N2 adsorption-desorption, X-Ray Diffraction (XRD), Scanning Electron Microscopy-Electron Dispersive X-ray (SEM-EDX), and Fourier Transform Infrared (FTIR) were adopted to characterize the activated carbon properties. The activated carbon formed was then coated with copper. The activity of the catalytic converter using activated carbon coated with copper was then tested for its performance on diesel engine Yanmar TF 70 LY-DI with variations in the number of catalyst layers, namely 1 layer (C1), 2 layers (C2) and 3 layers (C3). Sample with three layers (C3) of catalyst exhibited the highest activity with the percentage efficiency in reducing emissions concentration of 48.76 %; 31.27 % and 29.35 % for NOx, NO and CO, respectively.